Efficacy of insecticides for suppressing pod borer of mungbean - Shahiduzzaman, M; Nag, BL; Bashar, HMK; Hasan, GN (Bangladesh Journal of Agricultural Research, 2018)
A field experiment was carried out at Regional Pulses Research Station (RPRS), Madaripur during Kharif-I season of 2014 and 2015 to find out the effective insecticides for suppressing pod borer (Helicoverpa armigera Hubner) (Lepidopetera: Noctuidae) infesting Mungbean. In Kharif-I, 2014, suppression of pod borer infestation was the highest (80.82%) in Tracer (Spinosad) treated plot and produced the highest (1738 kg-1ha) seed yield and the highest benefit cost ratio (6.28) obtained in Volium Flexi 300SC (Thiamethaxam+ Chlorantraniliprole) treated plot. In Kharif-I, 2015, suppression of pod borer infestation was the highest (64.15%) in Volium Flexi 300SC treated plot and produced the highest (1610 kg-1ha) seed yield and also gave the highest benefit cost ratio (4.27). Considering the two years data the treatment Volium Flexi 300SC was found to be the best to suppress pod borer attacking mungbean. Bangladesh J. Agril. Res. 42(4): 725-730, December 2017